Hematological Profile of Tilapia (Oreochromis niloticus) as a Bioin-dicator to Evaluate Water Quality of Floating Net Cage Cultivation System in Ranu Grati, Indonesia - Alfarisi, Muhammad Asnin; Hertika, Asus Maizar Suryanto; Yanuhar, Uun (Department of Aquaculture, 2025)
Ranu Grati is a volcanic lake situated in Grati District, Pasuruan Regency, East Java, Indonesia. The rapid expansion of floating net cage aquaculture in Ranu Grati has raised concerns about water quality deterioration and its impact on fish health. This study aimed to evaluate the hematological profile of tilapia (Oreochromis niloticus) as a bioindicator for assessing water quality in floating net cage cultivation systems. The purpose of this research was to examine the hematological profile of tilapia fish alongside a series of water quality parameter measures as an environmental factor influencing fish life. Sampling was conducted with three repetitions every three weeks from September to November 2024 at five distinct locations, which were deemed representative of each group of floating net cages distributed around the Ranu Grati region. The Canonical Correspondence Analysis (CCA) approach was utilized to ascertain the relationship between hematological profile of tilapia and water quality. The data analysis indicates that the water quality at Stations 2 and 3 in the research area was somewhat polluted, but Stations 1 and 5 were heavily polluted. The elevated pollution levels at Stations 1 and 5 are attributed to the significant quantity of floating net cages in the vicinity relative to other stations. The investigation indicated that low dissolved oxygen levels and elevated ammonia concentrations impacted the hematological parameters of Tilapia fish. All water quality characteristics influenced the status of leukocytes, erythrocytes, and hemoglobin at moderate quantities. Moreover, micronuclei and hematocrit levels were significantly affected by elevated concentrations of ammonia, temperature, BOD, and pH, whereas DO, TDS, and TSS influenced lower values.